1979
DOI: 10.1139/b79-111
|View full text |Cite
|
Sign up to set email alerts
|

Papilla response of barley epidermal cells caused by Erysiphe graminis: rate and method of deposition determined by microcinematography and transmission electron microscopy

Abstract: ZEYEN, R. J.. ;111d W. R. BUSHNELL. 1979. response of barley epidermal cells causecl by Et:~,.si/~hr gr~trri~irri.~: I-ate and method of deposition determined by rnicrocinemutogfi~phy and tr':~nsmission electron mic~'oscopy. Can. J. Bot. 57: 898-913. Papillae were cleposited in barley epitle~mal cells directly heneath appressoria of Et:vsiplrt, gt.o/irirli.c f. sp. Irordri anti appeal-ed as hemispherical, intel-nal wall appositions. The papilla {response began shortly after the formation of a ~.apitlly movin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 13 publications
5
60
0
Order By: Relevance
“…This compartment was seen to accumulate in the vicinity of papillae. We speculate that this PEN1-related compartment might correspond to the "large vesicles" described previously in the defense literature (Zeyen and Bushnell, 1979;Hü ckelhoven et al, 1999) and that PEN1 might mediate its fusion at infection sites during papilla formation.…”
Section: A Role For Pen1 In Papilla Formationsupporting
confidence: 61%
See 2 more Smart Citations
“…This compartment was seen to accumulate in the vicinity of papillae. We speculate that this PEN1-related compartment might correspond to the "large vesicles" described previously in the defense literature (Zeyen and Bushnell, 1979;Hü ckelhoven et al, 1999) and that PEN1 might mediate its fusion at infection sites during papilla formation.…”
Section: A Role For Pen1 In Papilla Formationsupporting
confidence: 61%
“…The latter possibility, though unexpected, is consistent with the observation of GFP-PEN1 fluorescence in the apparent interior of the papillar structure. Unusual trafficking and fusion events, involving the fusion of unusually large "vesicles" 1 m in diameter at the papillae, have been reported during papilla formation (Zeyen and Bushnell, 1979), and such compartments have been shown to target reactive oxygen species toward infection sites (Hü ckelhoven et al, 1999). Collins et al (2003) report a decrease in the number of large vesicles observed at sites of failed penetration by the fungus in pen1 mutants.…”
Section: A Role For Pen1 In Papilla Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Near the contact area various modifications of the cell walls ('altered walls', 'haloes' and autofluorescence) have been observed (Ride & Pearce, 1979;Koga, Mayama & Shishiyama, 1980;Aist & Israel, 1986;Heath & Stumpf, 1986;Parry & Carver, 1986). Ultrastructural observations reveal an enhanced electron contrast in these regions (Kunoh et al, 1979;Zeyen & Bushnell, 1979). Material is often deposited at the inner side of the external cell wall at the site of infection, forming a so-called papilla which can be induced even before the fungus penetrates (Stanbridge, Gay & Wood, 1971;McKeen & Rimmer, 1973;Aist & Israel, 1977) and is associated with a cytoplasmic aggregation at the interface site (Heath, 1980; Stolzenburg, Aist & Israel, 1984).…”
Section: Introductionmentioning
confidence: 98%
“…Thus, it is likely that a rapid fusion of the membrane of spherosomes to the plasmalemma allows for the osmiophilic contents of the vesicles to be deposited into the developing papilla. This would result in papilla enlargement within 20-30min after the initiation of cytoplasmic aggregation2, 5,8,20). Zeyen and Bushnell20) observed papilla formation in living barley coleoptiles inoculated with E. graminis and reported that papillae were deposited rapidly for an initial 20-min period after initiation of cytoplasmic aggregation, by which time they had attained 80% of their final area, and they showed little growth after the first 30min.…”
Section: Introductionmentioning
confidence: 99%